Manajemen Program Keterampilan Multimedia Pada Madrasah Unggul - Aprilia Eka Cahyani; Ahmadi Ahmadi (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Ponorogo, 2023)
The multimedia skills program is one of the efforts to improve the quality of education by providing space for students to hone and develop their interests and talents. Currently, many high school and madrasah aliyah graduates do not have skills that can help in their lives. This study aims to determine the planning, implementation and evaluation of multimedia programs implemented in schools. This research uses qualitative research methods with the type of case study. Data collection techniques used interviews, observation, and documentation with data analysis techniques using data reduction, data presentation, and data verification. The results showed that first, the planning of the multimedia skills program begins with determining the components of program implementation, namely by formulating program objectives, compiling curriculum, selecting teacher educators, selecting students, procuring learning support infrastructure, and financing. Second, the implementation of the multimedia skills program refers to the Decree of the Director General of Islamic Education in 2020. The multimedia skills program is implemented in the learning process using theoretical learning methods and practical learning methods. Third, the evaluation of the implementation of the multimedia skills program is carried out with two kinds of evaluation, namely program evaluation carried out by holding a joint meeting with madrasah stakeholders once a semester and learning evaluation carried out by teacher educators carried out at the middle and end of the semester.